MANAJEMEN PRODUKSI DAN PEMASARAN PRODUK TAHU KURING PADA HOME INDUSTRY TAHU KURING MAKASSAR - Aladin, Andi; Modding, Basri; Syarief, Takdir; Wiyani, Lastri (Jurnal Dinamika Pengabdian, 2020)
Kuring tofu factory in Makassar / Gowa (South Sulawesi Province) is one of the home industries producing tofu from soybean raw materials that has been pioneered since 2017. The form of the curing tofu business is still very simple, the tofu production process is still simple, not yet regulated according to ideal needs. Likewise, special clothing equipment for production and packaging employees is not standard. The marketing system is still simple, market reach is still limited. In service activities by the UMI Makassar lecturer team funded by DRPM RISTEK-BRIN on the PKM (Community Partnership Program) scheme aims to help develop partners in the Makassar Kuring tofu factory business group to be more economically independent, improve their thinking and innovation skills. Service activities undertaken are to help deal with two main priority issues, namely: (1) Production Problems, which are related to production methods based on hygienic principles of the product, including production space management; (2) Marketing management issues. From the results of these service activities, increased partner empowerment, in this case increased production system arrangements, increased marketing reach, and finally increased turnover from sales of tofu preservative products from three million rupiahs per day to four point five million rupiahs per day (increased to 50%).   Keywords: Kuring tofu, production, marketing management, increased turnover.   ABSTRAK. Pabrik “Tahu Kuring” di Makassar/Gowa (Sulawesi Selatan) merupakan salah satu home industry yang meproduksi tahu dari bahan baku kedelai yang dirintis sejak tahun 2017. Bentuk usaha tahu kuring ini masih sangat sederhana, proses produksi tahu masih sederhana, belum tertata sesuai kebutuhan ideal. Begitu pula perlengkapan pakaian khusus untuk karyawan produksi dan pengemasan belum standar. Sistem pemasaran masih sederhana, jangkauan pasar masih terbatas. Dalam kegiatan pengabdian oleh tim dosen UMI Makassar yang dibiayai oleh DRPM RISTEK-BRIN pada skema PKM (Program Kemitraan Masyarakat) bertujuan membantu mengembangkan Mitra kelompok usaha pabrik tahu kuring Makassar untuk dapat lebih mandiri secara ekonomi, meningkatkan skill ketrampilan berfikir dan berinovasi. Aktifitas pengabdian yang dilakukan adalah membantu dalam penanganan dua permalahan prioritas utama yaitu: (1) Permasalahan produksi, yaitu yang berhubungan metode berpoduksi berdasarkan prinsip-prinsip higienitas produk, termasuk penataan ruang produksi; (2) Permasalahan manajemen pemasaran. Dari hasil kegiatan pengabdian ini berdampak pada adanya peningkatan keberdayaan mitra, dalam hal ini adanya peningkatan penataan system produksi, peningkatan jangkauan pemasaran, dan pada akhirnya peningkatan omzet dari hasil penjualan produk tahu kuring dari tiga juta rupiah perhari menjadi empat koma lima juta rupiah perhari (meningkat menjadi 50%).     Kata kunci: Tahu kuring, produksi, manajemen pemasaran, kenaikan omzet.